Interface Interaction Dependent Growth of Carbon Nanostructures: An In Situ Study (Adv. Mater. Interfaces 19/2022). Issue 19 (4th July 2022) - Zhang, Xiaofang; Tian, Dongliang; Yang, Feng; Zhao, Haofei; Lau, Woon‐Ming; Wang, Rongming
Abstract : Controllable Growth of Carbon Nanostructures In article number 2200334, Xiaofang Zhang, Rongming Wang, and co‐workers demonstrate controllable growth of graphite shells (GSs) and bamboo carbon nanotubes (CNTs) by adjusting the interface interaction between catalyst and substrate via temperature, i.e., high temperature favores tip‐growth of bamboo CNTs with larger catalyst nanoparticles, and low temperature favores base‐growth of GSs with smaller nanoparticles, which is revealed via in‐situ pyrolysis of Co phthalocyanine in an aberration‐corrected ETEM.